The tracheostomy clinical nurse specialist: an essential member of the multidisciplinary team. Issue 2 (February 2014) - Crosbie, R; Cairney, J; Calder, N
Abstract Background: Tracheostomies are a common procedure within the specialties of otolaryngology and intensive care. The ENT department at Monklands Hospital has developed the position of tracheostomy clinical nurse specialist to improve the management of tracheostomy patients. There is evidence to support the development of a multidisciplinary team for the management of tracheostomy patients following intensive care unit treatment; however, the creation of a specific tracheostomy clinical nurse specialist position has not been widely endorsed in the literature. Objective: This paper describes the role of the tracheostomy clinical nurse specialist, advocating this position within the multidisciplinary team.